Research Advances of Wnt Signaling Pathway in Ischemic Disease of Lower Extremity - Jinhui PENG; Weidong ZHU; Qirong QIAN (康复学报)
This review summarized the knowledge of Wnt signaling pathway and the research situation of ischemic diseases of lower extremity, then further analyzed the research advances of Wnt signaling pathways in ischemic disease of lower extremity. This article would provide theoretical proofs from the Wnt signaling pathway to explore the new ways on the treatment for ischemic disease of lower extremity.